Optimal dispatch of integrated energy system considering time-space dimensional demand response based on time-of-use electricity price - Cheng, Tingli; Zeng, Liqiang; Tang, Hao; Zhang, Yingying (Frontiers in Energy Research, 2025)
Demand response has significant potential for enhancing energy utilization, thereby contributing to the advancement of integrated energy systems (IES). In this paper, an optimal IES dispatch model fully incorporating flexible loads on the demand sides is established. Firstly, based on time-of-use (ToU) electricity pricing, a flexible two-dimensional integrated demand response (IDR) model is presented, which is characterized by considering tightly spatial-temporal coupling characteristics of different loads. Subsequently, a day-ahead dispatch model for IES, incorporating ToU-based IDR, is developed to minimize the total operational cost. In this model, the optimal ToU pricing scheme is determined by comparing their economic efficiencies. The Particle Swarm Optimization (PSO) algorithm is then applied to solve the complex dispatch problem. Finally, the case study is conducted and the comparative results confirm that: 1) implementation of the IDR in time-space dimension can flatten the loads curves; 2) the time-space IDR significantly promotes the economic benefits of IES dispatch; 3) the proposed dispatch model is able to coordinate and optimize various types of energy and flexible loads.